Evaluation of the genotoxic potential of protoporphyrin IX and the safety of a protoporphyrin IX‐rich algal biomass - Murbach, Timothy S.; Glávits, Róbert; Moghadam Maragheh, Niloofar; Endres, John R.; Hirka, Gábor; Goodman, Richard E.; Lu, Guihua; Vértesi, Adél; Béres, Erzsébet; Pasics Szakonyiné, Ilona (Journal of applied toxicology, 2022)
Chlamydomonas reinhardtii is a nonpathogenic, nontoxigenic green algae used as a sustainable source of protein in foods. In order to mimic meat‐like qualities, a strain rich in protoporphyrin IX (PPIX), an endogenous heme/chlorophyll precursor, was developed using an evolution and selection strategy, and investigations were carried out to evaluate the safety of the novel strain, C. reinhardtii (red), strain TAI114 (TAI114). Digestibility and proteomic evaluations were conducted to determine whether any potentially allergenic or toxic proteins occurred as the result of the mutation process. The genotoxic potential of pure PPIX was evaluated using a bacterial reverse mutation test, an in vitro mammalian chromosomal aberration test, and an in vivo mammalian micronucleus test. Finally, the novel TAI114 biomass was evaluated for general toxicity and identification of target organs in a 90‐day repeated‐dose oral toxicity study in rats. All proteins were rapidly degraded in pepsin at pH 2.0 suggesting low allergenic potential. The proteomic evaluation indicated that TAI114 biomass contains typical C. reinhardtii proteins. PPIX was unequivocally negative for genotoxic potential and no target organs or adverse effects were observed in rats up to the maximum feasible dose of 4000 mg/kg bw/day TAI114 biomass, which was determined to be the no‐observed‐adverse‐effect‐level (NOAEL). These results support the further development and risk characterization of TAI114 biomass as a novel ingredient for use in the meat analogue category of food. Protoporphyrin IX (PPIX) is an endogenous component of hemoglobin that can impart meat‐like qualities to non‐meat foods. An evolution and selection strategy was employed to develop a novel PPIX‐rich strain of the edible algae, Chlamydomonas reinhardtii. Before introducing the novel strain—TAI114—into food, preclinical safety studies were conducted and determined a low allergenic potential, lack of novel proteins, lack of genotoxic potential, and a subchronic no‐observed‐adverse‐effect‐level (NOAEL) in rats of 4000 mg/kg bw/day, the highest feasible dose.